In vitro antifungal potential of lactococcus lactis isolated from agricultural soils in terengganu against anthracnose pathogen, colletotrichum capsici - Fakri M.A.; Lani M.N.; Seng C.T.; Alias R.; Hassan Z. (Malaysian Society of Applied Biology, 2024)
Indexed by SCOPUS